2020
DOI: 10.1177/2050640620902956
|View full text |Cite|
|
Sign up to set email alerts
|

Safety and effectiveness of ustekinumab for induction of remission in patients with Crohn’s disease: A multicenter Israeli study

Abstract: Introduction Ustekinumab is an effective treatment of Crohn’s disease (CD). Real-world data addressing the efficacy and safety of ustekinumab are scarce. Aim Our aim was to assess the safety and efficacy of ustekinumab in a large national patient cohort. Methods A prospective multicenter study, in which we followed patients with active CD treated with ustekinumab for 24 weeks. Induction dose was intravenous ranging from 260 to 520 mg, according to body weight, followed by 90 mg doses given subcutaneously every… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
33
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 24 publications
5
33
0
2
Order By: Relevance
“…With regard to the data obtained at 24 weeks with obviously more consistent patient's numbers in all studies, 11,[18][19][20] percentages of steroid-free remission are more homogenous, with 40% in the present study and 38.3%, 11 38.4%, 19 35.1% in other studies, 19 with only one exception of 15%. 18 In the present study, disease severity at baseline in terms of HBI score was the only factor independently associated with failure to achieve steroid-free remission, both at weeks 24 and 52. Family history and a higher CCI at baseline were associated with failure to achieve steroid-free remission at week 24.…”
Section: Discussionsupporting
confidence: 78%
“…With regard to the data obtained at 24 weeks with obviously more consistent patient's numbers in all studies, 11,[18][19][20] percentages of steroid-free remission are more homogenous, with 40% in the present study and 38.3%, 11 38.4%, 19 35.1% in other studies, 19 with only one exception of 15%. 18 In the present study, disease severity at baseline in terms of HBI score was the only factor independently associated with failure to achieve steroid-free remission, both at weeks 24 and 52. Family history and a higher CCI at baseline were associated with failure to achieve steroid-free remission at week 24.…”
Section: Discussionsupporting
confidence: 78%
“…This is a considerably higher proportion likely due to a more diseaserefractory patient population when compared to the patients of IM-UNITI trial where only 23% needed dose adjustment from q12w to q8w [21]. Our data on dosing patterns support the findings of other real-world registry studies of ustekinumab maintenance treatment where the majority or all the patients commenced their ustekinumab maintenance therapy with q8w dosing [6,10,12,13,22]. Interestingly, data on recapturing or improvement of ustekinumab response in CD patients with q4w dosing is emerging [11,[22][23][24][25].…”
Section: Discussionsupporting
confidence: 74%
“…Furthermore, the patients have typically experienced several drug switches due to primary or secondary loss of response or intolerance [2]. While ustekinumab real-world studies have shown clinical benefit even in treatment-refractory CD patient cohorts, data on dosing patterns and dose optimization remain limited [6][7][8][9][10][11][12][13].…”
mentioning
confidence: 99%
“…UST is effective for treatment of Crohn's disease (CD) and ulcerative colitis 1‐4 . In addition to randomised controlled trials, multiple real‐world studies corroborated the effectiveness of UST in the treatment of CD 5‐19 . However, the risk of primary and secondary loss of response to UST has not been extensively reported.…”
Section: Introductionmentioning
confidence: 99%